Modelling and Simulation of Field Oriented Control Based Permanent Magnet Synchronous Motor Drive System - Faisal Amin; Erwan Bin Sulaiman; Wahyu Mulyo Utomo; Hassan Ali Soomro; Mahyuzie Jenal; Rajesh Kumar (Institute of Advanced Engineering and Science, 2017)
On the basis of analysis of dq model of permanent magnet synchronous motor (PMSM) and principle of field oriented control (FOC), detail modelling of PMSM drive system and simulation results presented in this paper. The PMSM model is based on electronic components rather than mathematical blocks, this enabled us to achieve simulation results more realistic. Moreover all the modules of this simulation, such as inverter and pwm generator are made from scratch instead of using premade Simulink blocks. Simulation was carried on the basis of step change in speed and torque then made performance comparison of several parameters such as abc current, dq current, speed and torque.